A Doctrinal and Newspaper Data Analysis of UK Policy for LGBTQ+ Asylum Seekers Following the Enactment of the Nationality and Boarders Act 2022 - Rachel Saunders (Societies)
The UK government has detailed guidelines for assessing and guiding LGBTQI+ asylum seekers through the asylum process in the UK. This is an explorative paper assessing whether post the enactment of the Nationalities and Boarders Act 2022 the media narrative around queer refugees has had any influence on UK government policy. It does this by laying out the baseline UK LGBTQ+ asylum seeker legislative and UK civil service guidance and analysing UK newspapers in a media data analysis of mainstream UK media websites to see if there is any media influence on legislation or guidance post-enactment of the NBA 2022. These findings indicate there was no discernible influence on UK government policy towards LGBTQ+ asylum seekers by mainstream UK news media (Mainstream media for this research is defined as national newspapers with large website traffic, such as The Guardian, The Times, and The Daily Mail. These sources were chosen due to their digital footprint and searchability, which enabled textual analysis of the content) post-enactment of the NBA 2022 on 28 April 2022. In addition, the doctrinal analysis shows that the UK government is both opaque about LGBTQ+ asylum statistics and the outcome of Stage 1 asylum decisions, making it difficult to judge what sources influence these decisions and data. This makes it difficult for the UK media to cover these stories with clarity unless a claimant waives their right to anonymity, or a leak happens. Given the available data, it is also apparent that there has been a year-on-year decrease in LGBTQ asylum appeals, suggesting that while the media narrative may not be influencing policy, the New Plan itself may be having a chilling influence on LGBTQ asylum claims. More research over a longer period of time is required to explore this.